PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - La Ode Anto; Safaruddin Safaruddin; Andi Zulkifli (Pascasarjana Universitas Halu Oleo, 2021)
This study aims to determine and analyze the effect of Corporate Social Responsibility (CSR) disclosure on company value of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sample in this study uses purposive sampling technique, from determining the sample obtained 12 sector manufacturing companies. various industries listed on the Indonesia Stock Exchange that meet the criteria to be sampled in this study. The data collection method uses documentation. Data analysis used descriptive statistical analysis and simple regression analysis. The results of this study indicate that the disclosure of Corporate Social Responsibility (corporate social responsibility) has a significant effect on firm value in various industrial sector manufacturing companies in the Indonesia Stock Exchange (BEI). This shows that the greater the disclosure of Corporate Social Responsibility (CSR), the greater the value of the company.